2020
DOI: 10.1111/bjet.13028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an immersive virtual reality‐based classroom on students’ learning performance in science lessons

Abstract: as well as a visiting scholar at Syracuse University from 2019 to 2020. Her primary research interests include emerging technologies for education. She has published several research papers in national and international journals, as well as presenting at a range of conferences. Lei Wang is currently a Ph.D. student in the Department of Instructional Design, Development and Evaluation at Syracuse University. Her research interests include technology integration to facilitate learning and teaching practices, tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(93 citation statements)
references
References 47 publications
3
85
0
5
Order By: Relevance
“…Therefore, face-to-face group learning activities combined with VR-supported interactive environments may provide a rich learning experience. In addition, visual descriptions of scienti c content and instant feedback from the intelligent robot in the virtual scene may enhance the conceptual development of scienti c knowledge [12]. The results also showed that students who worked in the e-learning group had a much higher academic achievement compared to students who learned through traditional teaching methods in a regular classroom.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, face-to-face group learning activities combined with VR-supported interactive environments may provide a rich learning experience. In addition, visual descriptions of scienti c content and instant feedback from the intelligent robot in the virtual scene may enhance the conceptual development of scienti c knowledge [12]. The results also showed that students who worked in the e-learning group had a much higher academic achievement compared to students who learned through traditional teaching methods in a regular classroom.…”
Section: Discussionmentioning
confidence: 95%
“…ECNU studies on the application of VR in face-to-face learning environments have identified an increase in the sense of students' presence and the relevance of visual processing in children's learning, revealing the importance of the use of new virtual technologies in curricula and teaching materials for these students. (Huang et al, 2020;Liu et al, 2020). As a way to better instruct pedagogy graduates on these technologies, ECNU developed for its pedagogy course the subject "Modern Education Technology," in which the main skills and competencies necessary for the use of ICT in teaching-learning are addressed (Lim et al, 2015).…”
Section: Academiamentioning
confidence: 99%
“…We also analyze that the study also can evaluate learning outcomes in the study (Porter et al 2020), student perception (Chamilothori et al 2019;Arias et al 2019;Pirker et al 2018;Abichandani et al 2019;O'Connor et al 2018;Greenwald et al 2018;Makransky et al 2020;Kersting et al 2020;Šiđanin et al 2020), Brain wave activity (Lamb et al 2018), and also can use both learning outcome and student perception Chang et al 2020;Liu et al 2020). Furthermore, we also analyze the trend of virtual reality usage in a broader theme of education and learning using the article record from different keywords after duplicate removed (951 studies).…”
Section: Overall Findingmentioning
confidence: 99%